Effects of berberine and red yeast on proinflammatory cytokines IL-6 and TNF-α in peripheral blood mononuclear cells (PBMCs) of human subjects - Spatuzza, Carmen; Postiglione, Loredana; Covelli, Bianca; Ricciardone, Margherita; Benvenuti, Claudio; Mondola, Paolo; Belfiore, Anna (Frontiers in Pharmacology, 2014)
Background and aims Obesity is a condition associated a chronic or an acute inflammatory response characterized by an increase of proinflammatory levels cytokines. In adipose tissue, mononuclear cells (MNCs) induce adipocytokines as IL-6 and TNF-α . The aim of this study was to investigate the effect of berberine (a natural alkaloid) and red yeast (a natural antioxidant) on cytokines IL-6 and TNF-α proteins and their genes expression, in circulating lipopolisaccarides (LPS) stimulated mononuclear cells (MNCs). Methods and results MNCs isolated from whole blood of healthly donors were stimulated with LPS to induce cytokines production; simultaneously cells were treated with increasing doses of Berberine and red yeast 1.5% S.C. (Specific Concentration) monacolin K alone or in association. The expression and transcription levels of IL-6 and TNF-α  were assessed by ELISA and real time PCR. Berberine plus red yeast treatment showed a marked synergic inhibitory effect on IL-6 expression, more evident at low concentration within a short time of application. These substances induced a synergic inhibition of TNF-α expression; concomitant treatment with berberine and red yeast inhibits IL-6 transcription at 3 and 24h, respectively. In the same way, TNF-α inhibition was statistically significant at 3h but not at 6 and 24h. Conclusions The results of our study show that both berberine and red yeast were able to carry out anti-inflammatory action trough an inhibition of proinflammatory protein concentrations, IL-6 and TNF-α, and their gene expression in MNCs activated by LPS. Therefore, these substances could represent a useful pharmacological treatment to reduce the proinflammatory status that is accompanied in obesity.